Revitalisasi Kurikulum PAI : dari Pendekatan Doktrinal ke Pendekatan Humanistik - Syaifudin Hadid; Chasanah Chasanah; Khuriyah Khuriyah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Revitalizing the Islamic Religious Education (PAI) curriculum is an important step towards improving the standard of Islamic Religious Education in line with contemporary demands. This research seeks to analyze the limitations of doctrinal methods and proposes a humanistic approach as a more appropriate alternative. Utilizing a literature review and qualitative methods, this article finds that the humanistic approach can effectively support the assimilation of values, encourage active engagement from students, and make learning more relevant and impactful. The development of Islamic Education curriculum through this humanistic approach paves the way for a more transformative model of Islamic Education that is in tune with students’ personal dimensions.